Pengaruh Keterampilan Komunikasi Efektif terhadap Perkembangan Bahasa Anak Usia Dini - Nurul Aini MM Sodik; Salwa Afrilla Patilima; Nuraini Mauke; Juwita Moodumbi (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
Communication within the family, especially between parents and children, is an important foundation for the development of a child's personality, emotions, and social skills. The purpose of this writing is to identify the types of parental communication styles, analyze the factors that influence them, examine their impact on child development, and provide practical recommendations to improve the effectiveness of communication patterns within the family. The method used in writing this paper is a literature study. The discussion results show that there are three main types of parental communication styles: permissive, authoritarian, and democratic. The permissive style tends to give the child unlimited freedom, the authoritarian style emphasizes control and obedience, while the democratic style encourages openness and mutual respect. The choice of communication style is influenced by various factors such as educational background, culture, past experiences, and the socio-economic conditions of parents. Each communication style has a different impact on the emotional, social, and cognitive development of children. The democratic style is considered the most effective in optimally supporting child development. This article provides recommendations to parents to increase knowledge about dialogical-based parenting, practice assertive communication skills, give children space to express their opinions, and build a family culture that is open and mutually respectful.